Penerapan Metode Drill and Practice dalam Pembelajaran Literasi Membaca pada Siswa Kelas XII SMA Unggulan Haf-Sa BPPT Genggong - Dewi Ananta; Muhammad Hifdil Islam; Hemas Haryas Harja Susetya (sarasvati, 2026)
This study aims to examine the application of the drill-and-practice method in reading literacy instruction for 12th-grade students at Haf-Sa BPPT Genggong High School by analyzing the implementation process of the method, the patterns of interaction between teachers and students, and various contextual factors that influence its implementation. This study employs a qualitative approach with a case study design focused on a single 12th-grade class during the reading literacy instruction process in the first semester of the 2025/2026 academic year. The research subjects consist of one Indonesian language teacher and six students selected through purposive sampling based on variations in reading literacy proficiency levels. Data collection was conducted through classroom observations over six sessions, semi-structured interviews, and a review of instructional materials and student exercise results. The results of the study indicate that the implementation of gradual, repetitive reading exercises contributes to the formation of systematic learning habits, increased precision in students’ comprehension of reading materials, and strengthened pedagogical feedback processes during instruction. However, the implementation of this method is also influenced by several constraints, such as limited instructional time, differences in students’ initial abilities, and the potential for burnout due to intensive practice. The findings indicate that the success of the drill-and-practice method is not solely determined by the repetition of exercises, but also depends heavily on the quality of instructional design, teachers’ adaptability, and effective pedagogical interaction.